(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Abstract: The stability of nutrients within foods is profoundly influenced by the food matrix—the intricate physical and chemical structure that defines how various components interact. This paper investigates the role of the food matrix in determining nutrient stability during both processing and storage. It highlights how different matrices, such as cellular structures in fruits and vegetables or lipid-rich environments, can either protect nutrients from degradation or exacerbate their loss. The review covers the impact of mechanical processing, chemical interactions, and processing conditions such as temperature and pH on nutrient stability. It also examines how storage factors, including humidity and light exposure, affect nutrient retention within different matrices. The paper explores the role of additives, such as antioxidants and preservatives, in interacting with the food matrix to either enhance or diminish nutrient preservation. Understanding these dynamics is crucial for optimizing food processing and storage methods to maximize nutrient retention and improve food quality. This comprehensive review provides insights into the complex relationships between the food matrix and nutrient stability, offering guidance for future research and practical applications in food science and technology.